Retrogressive Thaw Slumps Produce a Changing Disturbance Regime for Arctic Stream Invertebrates - Maria Dolan; Jordan Musetta‐Lambert; Krista S. Chin; Steven V. Kokelj; Suzanne E. Tank; Jennifer Lento; Michael Power; Joseph M. Culp (Global Change Biology, 2026)
For many Arctic rivers and streams, climate‐driven intensification of permafrost thaw slumping is a major source of disturbance to aquatic habitats. Thaw slumps are dynamic landforms that severely increase total suspended solids (TSS) and nutrients in downstream reaches and can persist over decades. Effects may differ in magnitude as slumps cycle through periods of higher and lower activity, with expansion of retrogressive slumps increasing over time. Increases in TSS are known to cause reduced invertebrate abundance and diversity in impacted watersheds; however, it remains unclear if water quality and critical aquatic biodiversity have recovered after prolonged exposure to slumps. Here, we examined decadal‐scale effects of slumps and environmental change on benthic macroinvertebrates (BMI) by comparing environmental and BMI data collected between 2010–2014 and a recent sampling campaign from 2021. High TSS and nutrient concentrations observed during 2010–2014 persisted in slump‐impacted sites in 2021, with no significant change in TSS and total nutrient concentrations after the 10‐year exposure period. TSS continued to act as a nonspecific stressor on BMI, as abundance remained significantly lower in impacted streams compared to reference streams. Although total abundance within reference and impacted sites did not differ significantly between sampling periods, abundance and richness of disturbance tolerant taxa was greater in 2021 as compared to 2010–2014 across all sites, with differences linked to lower precipitation in 2021. These community compositional changes were reflected in increased Shannon‐Weiner diversity between sampling campaigns. Overall, the number of thaw slumps upstream was an important driver of both BMI abundance and diversity across sampling periods and will likely continue to be an important determinant of benthic macroinvertebrate communities as the number and size of thaw slumps continues to increase across the circumpolar Arctic.